2002
DOI: 10.1515/jpem.2002.15.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Binding Protein, Insulin-like Growth Factor-I and Short Stature in Two Pygmy Populations from the Philippines

Abstract: The molecular basis and biochemical mediators of genetic growth propensity and adult height achievement in the general population are largely unknown. Pygmies represent one extreme of the height spectrum that may provide important clues regarding this issue. Previous studies in pygmies from Africa and Papua-New Guinea have shown decreased serum levels of growth hormone binding protein (GHBP), the circulating ectodomain of the growth hormone receptor (GHR). By inference, a similar limitation in tissue GHR expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Reports of relatively high morbidity rates in another negrito population, the Ati, suggest that the Aeta faced comparable conditions during the 1980s (Cadeliña and Cadeliña 1988). This supposition is consistent with serological data from the 1990s that indicate widespread undernourishment among the Aeta (Dávila et al 2002). Taken together, these lines of evidence suggest that the Aeta living on or near Mount Pinatubo endured relatively high rates of morbidity and mortality before 1991.…”
Section: Maternal Environment and Developmental Programmingsupporting
confidence: 84%
“…Reports of relatively high morbidity rates in another negrito population, the Ati, suggest that the Aeta faced comparable conditions during the 1980s (Cadeliña and Cadeliña 1988). This supposition is consistent with serological data from the 1990s that indicate widespread undernourishment among the Aeta (Dávila et al 2002). Taken together, these lines of evidence suggest that the Aeta living on or near Mount Pinatubo endured relatively high rates of morbidity and mortality before 1991.…”
Section: Maternal Environment and Developmental Programmingsupporting
confidence: 84%
“…Within a species and life history gamut, such as suggested by our preliminary research on humans, increases in body mass are at least partly accomplished by increasing the developmental rate within the same growth period and life history; i.e., the longperiod rhythm is shortened. Long-period rhythm variation relative to body mass thus offers a potential, if not partial, solution to questions of life history variation, while remaining cognizant of other genetic factors responsible for growth factors operating within what are otherwise restricted genetic/historical programs [28,29].…”
Section: Striae Of Retzius Repeat Interval Correlates With Body Massmentioning
confidence: 99%
“…Physiological evidence suggests that short stature is associated with low growth hormone binding protein and insulin-like growth factor-1 (IGF1) levels in Pygmy groups (Baumann et al 1989;Dávila et al 2002). Using high-density SNP chip data, several population genetic studies have reported candidates for Pygmy short stature, including genes in the IGF1 pathway (Pickrell et al 2009;Jarvis et al 2012;Migliano et al 2013), the iodine-dependent thyroid hormone pathway (López-Herráez et al 2009;Migliano et al 2013), and the bone homeostatsis/skeletal remodeling pathway (Mendizabal et al 2012).…”
mentioning
confidence: 99%